HUBUNGAN OPTIMISME MASA PERSIAPAN PENSIUN DENGANSINDROM PURNA KUASA PADA PEGAWAI NEGERI SIPIL (PNS) GURUDI KOTA MAKASSAR - Puji Rahayu; Widyastuti Widyastuti; Ahmad Ridfah (Jurnal Administrasi Negara, 2017)
The symptoms of post power syndrome are often experienced by individuals who are retired or has entered a period prior to retirement. This study aims to determine the relationship between optimism retirement preparation and post power syndrome. This study aims to determine the relationship of optimism during the preparation of retirement and post power syndrome. Research method is quantitative-associative. The population in this research is Civil Servant (PNS) of teachers in Makassar city and sampling of 29 people using accidental sampling technique, considering this research is non parametric where the sample may amount to less than 30 people. The result showed there is a negative relationship between optimism retirement preparation and post-power syndrome, r = - 0.822 (p = 0.000). That is, the higher the optimism of retirement preparation period, the lower the syndrome of powers on the teachers as civil servants. This suggests that there is a significant negative influence between optimism of retirement preparation period and post-power syndrome. This study implicates that it is necessary to instill an optimism attitude in order to face future retirement period as an attempt to avoid the post-power syndrome.